The Pseudomonas aeruginosa PA01 Gene Collection - LaBaer, Joshua; Qiu, QingQing; Anumanthan, Anukanth; Mar, Wenhong; Zuo, Dongmei; Murthy, T.V.S.; Taycher, Helen; Halleck, Allison; Hainsworth, Eugenie; Lory, Stephen; Brizuela, Leonardo (Genome Research, 2004)
Pseudomonas aeruginosa, a common inhabitant of soil and water, is an opportunistic pathogen of growing clinical relevance. Its genome, one of the largest among bacteria [5570 open reading frames (ORFs)] approaches that of simple eukaryotes. We have constructed a comprehensive gene collection for this organism utilizing the annotated genome of P. aeruginosa PA01 and a highly automated and laboratory information management system (LIMS)-supported production line. All the individual ORFs have been successfully PCR-amplified and cloned into a recombination-based cloning system. We have isolated and archived four independent isolates of each individual ORF. Full sequence analysis of the first isolate for one-third of the ORFs in the collection has been completed. We used two sets of genes from this repository for high-throughput expression and purification of recombinant proteins in different systems. The purified proteins have been used to set up biochemical and immunological assays directed towards characterization of histidine kinases and identification of bacterial proteins involved in the immune response of cystic fibrosis patients. This gene repository provides a powerful tool for proteome- and genome-scale research of this organism, and the strategies adopted to generate this repository serve as a model for building clone sets for other bacteria.
10.1101/gr.2482804